Preparation and characterization of inclusion complexes of β-cyclodextrin with 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][bf4])ionic liquid / Norashikin bt Othman - Othman, Norashikin (2013)
The interaction between β-cyclodextrin and ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF4]) had been studied. The inclusion complexation interaction was confirmed by FT-IR spectra. The inclusion complex was also characterized by 1H NMR, TGA and DSC. The results showed that the host-guest system presented a channel type structure and each glucose unit of β-cyclodextrin was in similar environment. The decomposition temperature of inclusion complex was lower than that of [bmim][BF4] and β- cyclodextrin individually. The ratio of 1:1 inclusion complex was determined in this study.